Implementation of a trauma and violence informed care elective to supplement early medical education - Trisha Agarwal; Anima Shrestha; Natasha Garamani; Rachael Williams (Discover Education)
Abstract Interpersonal violence (IPV) recognition is vital to patient-centered care. Previous educational efforts have incorporated IPV into undergraduate medical education in the form of standardized patient encounters and IPV screening and awareness, but no semester-long elective that offers an intersectional approach to trauma-informed care and incorporates local advocacy groups and resources currently exists. The aim of this elective was to address the gap in IPV education in current medical school curricula and equip first-year medical students with the skills and knowledge of trauma-informed approaches in healthcare settings. We implemented a Trauma and Violence Informed Care (TVIC) elective for first-year medical students at the University of Colorado School of Medicine during Fall 2022. Seventeen first-year medical students enrolled in the elective. In this 13-week program, students met twice weekly for 1 hour sessions consisting of lectures, group discussions and role-playing activities. Learning objectives addressed IPV, intersectionality, mandatory reporting, survivors' rights and resources, and vicarious trauma. To assess course impact, surveys with Likert scale and free-response questions were distributed. Responses were analyzed using paired T-tests and content analysis. All students completed the surveys. There was significant difference (p < 0.05) in student comfort and knowledge for the following topics: Skills & Abilities, Intersectionality, Resources, System Based Processes, and Course Logistics. A TVIC elective positively impacts medical student comfort and skills around IPV patient care. More educational efforts are needed to address this curricular gap.